"Anyone free to chat?" Using technological features to elicit quality support online. Issue 2 (3rd April 2018) - Youngvorst, Lucas J.; High, Andrew C.
ABSTRACT: This study examines how support seekers can integrate verbal and nonverbal cues in social network sites (SNSs) to elicit quality support from others. Building from sensitive interaction systems theory and verbal person centeredness (VPC), participants ( N = 579) evaluated a SNS profile that contained manipulated levels of directness in status updates used to seek support and nonverbal emotional expression in profile pictures. To capture the transaction of support, participants provided supportive messages in public and private conditions that were coded for their level of VPC. Negative emotional cues in profile pictures increased VPC in private messages, whereas directness in status updates negatively predicted VPC in private messages. Participants produced messages with higher levels of VPC after they viewed profiles that incorporated more features to disclose distress effectively. Broadly, this study addresses whether the content people post on SNS profiles shapes the quality of the supportive messages they receive.